The Randomized American Option as a Classical Solution to the Penalized Problem. (27th October 2015) - Leduc, Guillaume
Abstract : We connect the exercisability randomized American option to the penalty method by showing that the randomized American option valueu is the unique classical solution to the Cauchy problem corresponding to the canonical penalty problem for American options. We also establish a uniform bound forA u, whereA is the infinitesimal generator of a geometric Brownian motion.